Endophytic colonization of entomopathogenic Lecanicillium lecanii (Zimm) Zare & Gams PTN 10, and its effect on tobacco resistance against Myzus persicae Sulzer (Hemiptera: Aphididae). Issue 1 (January 2022) - Yuningsih, D; Anwar, R; Wiyono, S
Abstract: Lecanicillium lecanii is a potential effective entomopathogen against various insect pests. Some isolates of Lecanicillium is also reported as endophytic. However, the information on endophytic colonization of L. lecanii PTN 10 and its role in conferring tobacco resistance against Myzus persicae is not available. The objective of the research was to determine the endophytic colonization ability of L. lecanii on tobacco plants and its effect on the biology and population growth of Myzus persicae . This research consisted of four treatments i.e. untreated plants (K), seed treated with conidia suspension of L. lecanii for 12 hours (P1), foliar spray using conidia suspension L. lecanii one week after transplanting (P2), and the combination of seed treatments and foliar spray. All treated tobacco plants were infested by first nymph of M. persicae one week after L. lecanii treatment. The observations include aspects of biology i.e. life cycle, fecundity, and the longevity of M. persicae. L. lecanii is proven able to colonize tobacco leaves endophytically. The fungus treatment on tobacco plants causes a prolonged life cycle, decreases fecundity, and significantly shortens longevity. Additionally, it suppresses population growth of M persicae .